An Introduction to Radical Minimalism: On Merge and Transfer - Krivochen, Diego Gabriel (IBERIA: An International Journal of Theoretical Linguistics, 2011)
On this paper we will try to outline the basic tenets of Radical Minimalism, going deeper in the line of what we have said in previous papers. We will assume most of that framework, as well as orthodox Minimalism, and take that as a point of departure for new inquiries. We will test Radical Minimalism by analyzing what we consider to be the one and only generative mechanism in the human mind: the operation merge. We will review some work done about it and then present our own proposal, trying to derive the conceptual necessity and the properties of merge from interface conditions and then discuss the problem of labeling. On our way, we will also take the question of interpretable and uninterpretable features and the problem of valuation (Chomsky, 1999), and see if we can dispense with them in order to build a radically minimalist theory. We will also put our framework to test by presenting our theory of transfer, or derivation by phases in radically minimalist terms, which will implicate positing only principled operations and deriving everything from the dynamics of the derivation in interaction with interface requirements (see Boeckx 2010). Our ultimate goal will be to integrate the study of language (along with the study of any other mental faculty) in the study of the physical universe (or “natural world”), as a physical system among many others with which language should optimally share characteristics, operations and principles that we take to be universal. Keywords: Radical Minimalism, Merge, Transfer, phases, labels, quantum mechanics, features, licensing, interface conditions Palabras Clave: Minimalismo Radical, Ensamble, Transferencia, fases, etiquetas, mecánica cuántica, rasgos, licenciamiento, condiciones de interfaz